The use of the photography in the Spanish online dailys (Communication & Society, 2006)
The photography continues being one of the informative elements that has found more dificulties for getting an important function in Internet. It, although they have passed more than ten years from the arrival to the Network of first Spanish online newspapers. The present article analyzes the treatment that the photography receives in online editions of El País, ABC, La Vanguardia and El Mundo, and the changes that have taken place in this element during the last six years.